Urban geographies of romance: meeting and mating in Cairo - van Dalen, Elaine (AUC Knowledge Fountain, 2013)
This thesis offers a spatial analysis of engagement and marriage among young people from Būlāq ad-Dakrūr, Cairo. It explores how these individuals negotiate their access to spaces within a neoliberal city and use them to find potential partners, meet with those partners once they have found them and to live with them when they first get married. The researcher had informal conversations with about 30 individuals between the age 18 and 30 and their family members, mostly during the spring of 2013. The outcome shows that the neighborhood has a primary function in the shaping of gendered subjectivities that try to live up to the expectations in their community and therefore choose to act in certain ways in relation to engagement and partner finding. Though neighborhood etiquette prescribes that people of opposite sexes who are not related are not supposed to meet each other unless they’re married, young individuals creatively search for opportunities to meet with people of the other sex in spaces away from the eyes who can judge them about doing so. The mobility of young women, who often work in low-paid service jobs in more affluent adjacent areas and go to school outside their neighborhood, is central to new understandings of engagements as more temporal relationships that involve fun and romance and come to mean more than just official agreements between families. The anonymity of public spaces in the city offers possibilities of secrecy, privacy and adventure away from a neighborhood community whose moral expectations would otherwise restrict much of young people’s actions. While many spaces in the city have increasingly become privatized and mostly accessible to people with money, such as clubs and cafés, young poor people are yet creative to assert their right to the city and make use of those open places still available to their use. Many young women continue to use their ability to negotiate their freedom of movement within the spaces of their new house and outside of it after they marry.